PENGARUH INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM DI KOTA TERNATE - Ismail, Wardi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This study aims for analyze how influence inclusion finance and literacy finance to performance of Micro, Small and Medium Enterprises (MSMEs) in Ternate City. Election sample in study this use formula slovin and technique taking sample used is Probability sampling. Technique data collection is done use questionnaire, object in study this is SMEs in Ternate City. Test hypothesis in study this use analysis multiple linear regression with SPSS help. Results from study this is found that: (1) Influence inclusion finance influential to performance of Micro, Small and Medium Enterprises (MSMEs). Thus, the wider the financial information disclosure, the performance will increase and conversely, the narrower the financial disclosure, the more it will hinder the rate of performance improvement; (2) Literacy finance influential to performance of Micro, Small and medium Enterprises Medium (MSMEs). Thus, if business actors have good financial literacy, they will increase the business they run. With financial literacy, people are able to allocate their finances well.